2021
DOI: 10.1101/2021.11.29.470432
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-task representations in human cortex transform along a sensory-to-motor hierarchy

Abstract: Human cognition recruits diverse neural processes, yet the organizing computational and functional architectures remain unclear. Here, we characterized the geometry and topography of multi-task representations across human cortex using functional MRI during 26 cognitive tasks in the same subjects. We measured the representational similarity across tasks within a region, and the alignment of representations between regions. We found a cortical topography of representational alignment following a hierarchical se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 69 publications
2
10
0
Order By: Relevance
“…2i) -systems that are functionally distinct/specialized from each other -we found a monotonic relationship between these systems and their gradient loading. This is consistent with a gradient of functional specialization, where sensory and motor regions are defined by distinct functions, while association regions integrate the two (Ito and Murray, 2021). Moreover, this sensory-to-motor SC gradient was significantly associated with the 2nd principal gradient of rNC (rank r=0.72, non-parametric p<0.001) (Fig.…”
Section: Cortical Scs Are Organized Along a Gradient Of Functional Sp...supporting
confidence: 82%
See 2 more Smart Citations
“…2i) -systems that are functionally distinct/specialized from each other -we found a monotonic relationship between these systems and their gradient loading. This is consistent with a gradient of functional specialization, where sensory and motor regions are defined by distinct functions, while association regions integrate the two (Ito and Murray, 2021). Moreover, this sensory-to-motor SC gradient was significantly associated with the 2nd principal gradient of rNC (rank r=0.72, non-parametric p<0.001) (Fig.…”
Section: Cortical Scs Are Organized Along a Gradient Of Functional Sp...supporting
confidence: 82%
“…Portions of this section are paraphrased from the dataset's original publication's Methods section (King et al, 2019), and a prior study we used to investigate multi-task cortical representations (Ito and Murray, 2021).…”
Section: Multi-domain Task Battery Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…b) To match the number of layers in the ANN, we created three discretized systems based on the functional network partition -sensory, association, and motor -that followed the sensory-to-motor hierarchy (Fig. 8) [32,21] Supplementary Figure 7: A pairwise comparison of PS for all possible dichotomies in the Logic rule condition. a) We computed the PS for every pairwise dichotomy in the Logic rule domain, and computed the average PS across brain regions within each cortical system (Sensory, Association, and Motor cortex).…”
Section: A Supplementary Methodsmentioning
confidence: 99%
“…Analysis of human fMRI data revealed that content-specific abstraction was spatially heterogeneous across cortex. Recent neuroscience work has identified hierarchical gradients that organize along a sensory-to-motor output axis in both resting-state [32] and multi-task fMRI data [21]. We therefore sought to quantify PS across this sensory-to-motor hierarchy in fMRI data, and compare it to PS changes in the feedforward hierarchy (i.e., layer-depth) in ANNs.…”
Section: Convergent Hierarchy Of Abstract Representations In Humans A...mentioning
confidence: 99%